Modeling of soil water and nitrogen transport characteristics of the furrow irrigation for urea fertilizer using HYDRUS - Feng, Zhengjiang; Nie, Weibo; Ma, Yunpeng (International Journal of Agricultural and Biological Engineering, 2025)
Furrow irrigation is widely used in agriculture practice but faces challenges in inefficient water and nitrogen management, which may contribute to groundwater contamination risks due to nitrate leaching. In this study, soil hydraulic and solute reaction parameters were inversed through HYDRUS-1D and genetic algorithm based on one-dimensional urea solution infiltration experiments to explore the effects of urea concentration (C), water depth (WD), furrow bottom width (FW), and soil initial water content (IWC) on soil water and nitrogen transport characteristics of furrow irrigation using HYDRUS-2D simulation. Moreover, structural equation modeling (SEM) quantitatively analyzed these factors. The results showed that the inversed parameters were reliable. The infiltration rate increased with C, WD, and FW but decreased with IWC. The urea was completely hydrolyzed on the fifth day of the redistribution process. The ammonium nitrogen (NH_4^+-N) initially increased to the maximum value on the third day and then decreased. The SEM revealed that the IWC, FW, and WD positively affected the aspect ratio of the wetting pattern. It is suggested that WD and FW should be appropriately increased during furrow irrigation. Moreover, to reduce the risk of deep leaching of NO_3^–N, fertigation should be avoided when the soil water content is high in the range of suitable water contents for crop growth. The results provide theoretical insights for improving nitrogen efficiency and supporting sustainable agricultural practices. Key words: urea concentration; furrow irrigation; HYDRUS; NO3–-N leaching DOI: 10.25165/j.ijabe.20251802.8850 Citation: Feng Z J, Nie W B, Ma Y P. Modeling of soil water and nitrogen transport characteristics of the furrow irrigation for urea fertilizer using HYDRUS. Int J Agric & Biol Eng, 2025; 18(2): 169–178.